Gene Polymorphisms and the Prevalence of Key Periodontal Pathogens - Nibali, L.; Ready, D.R.; Parkar, M.; Brett, P.M.; Wilson, M.; Tonetti, M.S.; Griffiths, G.S. (Journal of dental research, 2007)
Growing evidence suggests that individual genetic susceptibility may influence the host’s response to infections. The aim of this project was to study whether gene polymorphisms of inflammatory markers are associated with the presence of viable periodontopathogenic bacteria. We extracted genomic DNA from 45 young adults diagnosed with generalized aggressive periodontitis to study Fc receptors, formyl peptide receptor, Interleukin-6, tumor necrosis factor-α, and vitamin D receptor polymorphisms. The presence and viable numbers of Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, and Tannerella forsythensis were determined by culture, and their identities confirmed by PCR. Multiple logistic regressions revealed that both Fcγ receptor and IL-6 -174 polymorphisms were associated with increased odds of detecting A. actinomycetemcomitans, P. gingivalis, and T. forsythensis after adjustment for age, ethnicity, smoking, and periodontitis extent. These findings support the hypothesis that complex interactions between the microbiota and host genome may be at the basis of susceptibility to aggressive periodontitis.